Electromagnetic navigated condylar positioning after high oblique sagittal split osteotomy of the mandible: a guided method to attain pristine temporomandibular joint conditions - Berger, Moritz; Nova, Igor; Kallus, Sebastian; Ristow, Oliver; Eisenmann, Urs; Dickhaus, Hartmut; Engel, Michael; Freudlsperger, Christian; Hoffmann, Jürgen; Seeberger, Robin (Oral surgery, oral medicine, oral pathology and oral radiology, 2018)
Objectives Reproduction of the exact preoperative proximal-mandible position after osteotomy in orthognathic surgery is difficult to achieve. This clinical pilot study evaluated an electromagnetic (EM) navigation system for condylar positioning after high-oblique sagittal split osteotomy (HSSO). Study Design After HSSO as part of 2-jaw surgery, the position of 10 condyles was intraoperatively guided by an EM navigation system. As controls, 10 proximal segments were positioned by standard manual replacement. Accuracy was measured by pre- and postoperative cone beam computed tomography imaging. Results Overall, EM condyle repositioning was equally accurate compared with manual repositioning (P > .05). Subdivided into 3 axes, significant differences could be identified (P < .05). Nevertheless, no significantly and clinically relevant dislocations of the proximal segment of either the EM or the manual repositioning method could be shown (P > .05). Conclusions This pilot study introduces a guided method for proximal segment positioning after HSSO by applying the intraoperative EM system. The data demonstrate the high accuracy of EM navigation, although manual replacement of the condyles could not be surpassed. However, EM navigation can avoid clinically hidden, severe malpositioning of the condyles.